C-C motive chemokine ligand 2 and thromboinflammation in COVID-19-associated pneumonia: A retrospective study. Issue 204 (August 2021) - Nieri, Dario; Neri, Tommaso; Barbieri, Greta; Moneta, Sara; Morelli, Giovanna; Mingardi, Desirè; Spinelli, Stefano; Ghiadoni, Lorenzo; Falcone, Marco; Tiseo, Giusy; Menichetti, Francesco; Franzini, Maria; et al.
Abstract: Purpose: A derangement of the coagulation process and thromboinflammatory events has emerged as pathologic characteristics of severe COVID-19, characterized by severe respiratory failure. CC motive chemokine ligand 2 (CCL2), a chemokine originally described as a chemotactic agent for monocytes, is involved in inflammation, coagulation activation and neoangiogenesis. We investigated the association of CCL2 levels with coagulation derangement and respiratory impairment in patients with COVID-19. Methods: We retrospectively evaluated 281 patients admitted to two hospitals in Italy with COVID-19. Among them, CCL2 values were compared in different groups (identified according to D-dimer levels and the lowest PaO2 /FiO2 recorded during hospital stay, P/Fnadir ) by Jonckheere-Terpstra tests; linear regression analysis was used to analyse the relationship between CCL2 and P/Fnadir . We performed Mann-Whitney test and Kaplan-Meier curves to investigate the role of CCL2 according to different clinical outcomes (survival and endotracheal intubation [ETI]). Results: CCL2 levels were progressively higher in patients with increasing D-dimer levels and with worse gas exchange impairment; there was a statistically significant linear correlation between log CCL2 and log P/Fnadir . CCL2 levels were significantly higher in patients with unfavourable clinical outcomes; Kaplan-Meier curves for the composite outcome death and/or need for ETI showed a significantly worse prognosis for patients with higher (> median) CCL2 levels. Conclusions: CCL2 correlates with both indices of activation of the coagulation cascade and respiratory impairment severity, which are likely closely related in COVID-19 pathology, thus suggesting that CCL2 could be involved in the thromboinflammatory events characterizing this disease. Highlights: CCL2 (also known as MCP-1) is involved in inflammation, angiogenesis, coagulation CCL2 can play a role in thromboinflammatory events in severe COVID-19 Increasing CCL2 levels correlate with D-dimer in COVID-19 Circulating CCL2 is associated with respiratory impairment severity in COVID-19 CCL2 is associated with unfavourable clinical outcomes in COVID-19 patients